2013
DOI: 10.1111/jfb.12081
|View full text |Cite
|
Sign up to set email alerts
|

Reach and catchment‐scale characteristics are relatively uninfluential in explaining the occurrence of stream fish species

Abstract: The objectives of this study were (1) to determine whether the presence or absence of prairie fishes can be modelled using habitat and biotic characteristics measured at the reach and catchment scales and (2) to identify which scale (i.e. reach, catchment or a combination of variables measured at both scales) best explains the presence or absence of fishes. Reach and catchment information from 120 sites sampled from 1999 to 2004 were incorporated into tree classifiers for 20 prairie fish species, and multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…One of our primary objectives was to draw inferences between landscape‐scale factors and species origin (native and non‐native) and reproductive strategy. Therefore, we used environmental data from online sources to develop model‐based hypotheses by measuring stream size and context variables and land cover at the reach scale, and geology and watershed size and disturbance variables like density of oil and gas wells at the watershed scale [hydrologic unit code (HUC) 10; Muellner et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…One of our primary objectives was to draw inferences between landscape‐scale factors and species origin (native and non‐native) and reproductive strategy. Therefore, we used environmental data from online sources to develop model‐based hypotheses by measuring stream size and context variables and land cover at the reach scale, and geology and watershed size and disturbance variables like density of oil and gas wells at the watershed scale [hydrologic unit code (HUC) 10; Muellner et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…As hypothesized, the performance of the models increased by including information on the hydromorphological state up- and downstream a sampling site, similar to other studies which found that fish metrics can be better explained by considering different spatial scales. For example, Wuellner et al [ 46 ] reported improved model performance to predict the presence of prairie fish species if information on reach and catchment scale are combined. Kail and Wolter [ 8 ] found significant effects of the hydromorphological state at the site, up- / downstream scale and catchment land use on a set of fish metrics including richness and abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the fish communities upstream and downstream of all crossing types may represent fishes that are mostly tolerant of disturbances in general. Many prairie fishes are categorized as generalists (Matthews, 1987;Bramblett & Fausch, 1991;Goldstein & Simon, 1999;Bramblett et al, 2005;Wuellner et al, 2013), and the frequency and duration of natural disturbances such as drought and anthropogenic disturbances such as intensive agriculture have favored the prevalence of tolerant taxa in prairie streams (Matthews, 1988;Bramblett et al, 2005). Fish communities, in general, could recover from road crossings over time (Peterson & Nyquist, 1972;Barton, 1977;Wellman et al, 2000;Vander Pluym et al, 2008), but the recovered community may represent an alternative stable state (Scheffer et al, 2001;Carpenter, 2002;Vander Pluym et al, 2008).…”
Section: Discussionmentioning
confidence: 99%